Facilitating the implementation of clinical technology in healthcare: what role does a national agency play? - Gill Harvey; Sue Llewellyn; Gregory Maniatopoulos; Alan Boyd; Rob Procter (BMC, 2018)
Abstract Background Accelerating the implementation of new technology in healthcare is typically complex and multi-faceted. One strategy is to charge a national agency with the responsibility for facilitating implementation. This study examines the role of such an agency in the English National Health Service. In particular, it compares two different facilitation strategies employed by the agency to support the implementation of insulin pump therapy. Methods The research involved an empirical case study of four healthcare organisations receiving different levels of facilitation from the national agency: two received active hands-on facilitation; one was the intended recipient of a more passive, web-based facilitation strategy; the other implemented the technology without any external facilitation. The primary method of data collection was semi-structured qualitative interviews with key individuals involved in implementation. The integrated-PARIHS framework was applied as a conceptual lens to analyse the data. Results The two sites that received active facilitation from an Implementation Manager in the national agency made positive progress in implementing the technology. In both sites there was a high level of initial receptiveness to implementation. This was similar to a site that had successfully introduced insulin pump therapy without facilitation support from the national agency. By contrast, a site that did not have direct contact with the national agency made little progress with implementation, despite the availability of a web-based implementation resource. Clinicians expressed differences of opinion around the value and effectiveness of the technology and contextual barriers related to funding for implementation persisted. The national agency's intended roll out strategy using passive web-based facilitation appeared to have little impact. Conclusions When favourable conditions exist, in terms of agreement around the value of the technology, clinician receptiveness and motivation to change, active facilitation via an external agency can help to structure the implementation process and address contextual barriers. Passive facilitation using web-based implementation resources appears less effective. Moving from initial implementation to wider scale-up presents challenges and is an issue that warrants further attention.